(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: Psoriasis can be a debilitating condition, but there may be a solution. Recently, several studied showed that emulsion-based topical drug delivery system could be a promising approach for the treatment of psoriasis. Hence, in the present study, Wrightia tinctoria (WT) oil-based emulgel was developed for the enhancement of effectiveness against psoriasis. Materials and Methods: This breakthrough treatment could be an alternative technique for the management of psoriasis. WT oil was used to prepare emulsions, which was loaded into a gel base. The concentration different excipients varied to prepare various emulsion formulations and evaluated for different parameters. The developed formulations were evaluated for the various parameters such as drug content, particle size, zeta potential, viscosity, pH and percentage drug release. Results and Discussion: The optimized formulation (F4) was found to have droplet size of 3218 ± 1.24 nm, 0.0175 ± 1.78 V zeta potential, entrapment efficiency of 59.53 ± 8.42%, and spreadability of 2.901 ± 0.12 mm. The pH and viscosity of optimized WT oil-based emulgel was found to be 6.1 ± 0.578 and 94,374 ± 198 cp, respectively. In vitro release of WT oil from optimized emulgel was found to be 98.87 ± 1.15% in 10 h. In 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide cytotoxicity study indicated no significant difference between the WT oil and its emulgel. Thus, suggested no loss of anti-proliferation activity of WT oil on formulation in emulgel. Conclusion: This study showed that the emulgel formulation has the potential to significantly enhance the efficacy of WT oil in treating psoriasis. These findings provide exciting new possibilities for improving psoriasis treatment and highlight the importance of continued research in this area.